Automated Verbalization of Conceptual Data Models in Bahasa Melayu and Mandarin - Lim, Shin Huei (2015)
This thesis focuses on the automated verbalization of conceptual data models using Object Role Modeling (ORM), specifically within the context of Asian languages—Bahasa Melayu and Mandarin. While ORM has proven effective in capturing complex business semantics, verbalizing such models in non-English languages remains a challenge in both academic and business practice. The research investigates how native linguistic structures affect the automated transformation of ORM diagrams into natural language sentences, aiming to bridge communication between domain experts and developers in multilingual environments. By extending the verbalization engine in the NORMA tool, the study introduces a prototype that supports Malay and Mandarin verbal outputs based on refined grammar rules, classifier patterns, and contextual sentence structures. Results from implementation and evaluation highlight improved clarity, simplicity, and precision in ORM verbalizations in both target languages, supporting the broader goal of making conceptual modeling more accessible to non-English-speaking stakeholders.